2023
DOI: 10.3390/nu15102365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Fiber on Inflammation and Insulin Resistance in Older Patients: A Narrative Review

Abstract: The beneficial impact of dietary fiber on the prevention and management of several chronic conditions associated with aging, including diabetes, neurodegenerative, cardiovascular diseases, and cancer, is well-known. High fiber intake has been associated with reduced inflammatory mediators counteracting the low-grade chronic inflammation typical of older age. In addition, dietary fiber improves postprandial glucose response and insulin resistance. In contrast, during acute diseases, its effects on insulin resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 108 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…However, this is not accurate. Carbohydrates such as fiber are beneficial to human and microbiome, resulting in the improvement in immune response, health, and ultimately affects aging [42,43]. Similar proposals were also found in fat, where it was commonly believed that fat is bad for health.…”
Section: Dietmentioning
confidence: 75%
“…However, this is not accurate. Carbohydrates such as fiber are beneficial to human and microbiome, resulting in the improvement in immune response, health, and ultimately affects aging [42,43]. Similar proposals were also found in fat, where it was commonly believed that fat is bad for health.…”
Section: Dietmentioning
confidence: 75%
“…The amount of fiber found in this study was higher than Kongkachuichai et al [ 27 ], who found 0.99 to 0.73 % in five Thai pomelo varieties. The fiber in food samples not only decreased or delayed the absorption of glucose into the blood but also increased insulin sensitivity by reducing hepatic liver content [ 28 ]. Therefore, the observed variance in proximate composition could potentially be attributed to a combination of regional variation, edaphic variables, climate fluctuations, and the genetic mix of individual fruit cultivars [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fiber offers various metabolic health benefits including increased satiety [13], reduced triglyceride absorption, and improved glycemic control [14,15]. Increased fiber intake has also been linked to blunted systemic inflammation [16,17], which often manifests with altered lipid and glucose metabolism. However, metabolic benefits vary by pulse variety, dosage, and duration of inclusion in the diet [15].…”
Section: Introductionmentioning
confidence: 99%